Armstrong on reinventing performance management : building a culture of continuous improvement - Armstrong, Michael, 1928- (Kogan Page, 2017)
"Armstrong on Reinventing Performance Management details how to build a culture of ongoing feedback and coaching and provides case studies of how this approach to building performance has been effective in organizations including Deloitte, Gap, Expedia and Google. Filled with practical advice, including how to deal with underperformers, it enables organizations to remove overly bureaucratic and ineffective systems based on top-down judgments and ratings, and demonstrates how to get line managers' support for the process focusing on actionable feedback and growth."--Resumé vydavatele